The Influence of Information System Quality and Service Quality on User Satisfaction with the BCA Mobile Banking Application among Generation Z - Khaerunisa Harsono; Vicky Dzaky Cahaya Putra (International Journal of Business, Economics, and Social Development, 2026)
The development of information technology has encouraged the banking sector to provide digital services, one of which is through mobile banking applications. BCA Mobile Banking serves as a solution to facilitate fast, secure, and flexible financial transactions, particularly for Generation Z, who have a high dependency on digital technology. However, in practice, various user complaints are still found, such as application errors, login failures, OTP system disruptions, and transaction issues that may potentially reduce user satisfaction. This study aims to analyze the influence of information system quality and service quality on user satisfaction with the BCA Mobile Banking application among Generation Z. The research method employed is a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 Generation Z respondents who are active users of BCA Mobile Banking, selected using a non-probability sampling technique with quota sampling. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS version 26 software. The results indicate that information system quality and service quality have a positive and significant effect on user satisfaction, both partially and simultaneously. Partially, information system quality and service quality each have a significant effect on user satisfaction. Simultaneously, these two variables are able to explain 53% of user satisfaction, while the remaining percentage is influenced by other factors beyond the scope of this study. These findings emphasize that improving information system quality and service quality is an important factor in enhancing user satisfaction with the BCA Mobile Banking application among Generation Z.